Association of Different Forms of Child Maltreatment With Peer Victimization in Mexican Children and Adolescents - Martín-Babarro, Javier; Toldos, M. Paz; Paredes-Becerra, Lorena; Abregu-Crespo, Renzo; Fernández-Sánchez, Juan; Díaz-Caneja, Covadonga M. (Frontiers in Psychology, 2021)
Objective: To examine the relationship between exposure to multiple forms of child abuse and neglect within the family context and peer victimization at school, accounting for the moderator effect of sex and educational level. Methods: Two thousand four hundred fifteen children and adolescents, aged 9 to 15 years, attending public schools in Mexico completed the Childhood Trauma Questionnaire-Short Form and a modified version of the Olweus' Bully/Victim Questionnaire. We used linear regression models to assess the association of five different forms of child abuse (emotional, physical, and sexual abuse, and emotional and physical negligence) with three forms of peer victimization (direct, indirect, and cyberbullying). Results: Direct forms of child abuse within the family (i.e., emotional, physical, and sexual abuse), but not neglect, were significantly and positively associated with a risk for peer victimization. In the fully adjusted models, emotional abuse was significantly associated with the three types of peer victimization: [indirect b = 0.48, t = 6.75, p < 0.001, direct (b = 0.47, t = 4.89, p < 0.001), and cyberbullying (b = 0.85, t = 5.45, p < 0. 001)]; while physical abuse was positive and significantly associated with direct victimization (b = 0.29, t = 3.28, p < 0.001). Boys suffering from sexual abuse within the family context showed higher levels of all subtypes of peer victimization. Students attending secondary school who suffered from sexual abuse showed higher levels of indirect victimization than did students attending primary schools. Conclusion: Child abuse within the family context seems to be associated with the risk of peer victimization. Preventive strategies to address bullying and promote resilience should take family factors into account. Interventions for high-risk families might be useful to prevent child multi-victimization.